KAJIAN KRITIK TERHADAP NOVEL “THE SATANIC VERSES” KARYA SALMAN RUSHDI - H. Abd. Safa, Najamuddin (JURNAL ILMU BUDAYA, 2014)
This article studies the novel "The Satanic Verves" by Salman Rushdie. The approach used inthis study is literary criticism in general and Islamic literary in particular. In studies, the writerdescribes contents and purpose of the novel. Actually, Islam accepts all forms of art and literatureto advance human life, to strengthen the Islamic faith, and consequently to support the truemethodology of the art. Based on these methodologies and principles, this novel cannot beconsidered as a literary, since the novel only insults Islam and its followers, even contemptfollowers of other religions and mankind as a wholeKeywords:Abstrak: Kajian Kritik Terhadap Novel “The Satanic Verses” Karya Salman Rushdi